Description of a new Betylobraconini-like parasitoid wasp genus and species (Hymenoptera: Braconidae: Rogadinae) from Chile - Quicke, Donald L. J.; Butcher, Buntika A. (Zootaxa, 2015)
Gondwanocentrus gen. nov. (type species Gondwanocentrus humphriesi sp. nov.) from Chile is described and illustrated. Morphological and weak molecular evidence indicate that the new genus may be a basal member of the Betylobraconini. The molecular data analysed to assess its placement additionally draw into question the relationship between Betylobraconini and Clinocentrini. Previously, the Betylobraconini were known only from the Australasian region, Oceania and Eocene Europe (Baltic amber), thus if Gondwanocentrus gen. nov. does belong to this group it confirms the groups present day Gondwanan distribution.